The trails - the roots of the circumstantial paradigm - Ginzburg, Carlo (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
The circumstantial reasoning is a common and widely used way of acquiring inferences based on a very limited number of premises. This paradigm emerged as an epistemological model at the end of the 19th century but has not yet received any systematic theoretical treatment. The paradigm became famous as the 'Morelli method' utilized by the historians of art to identify the authorship of various pieces of art, paintings in particular. The method allows the identification based on the investigation of certain features that are unnoticeable to the majority of observers. The same procedure seems to be operational among hunters who are capable of reconstructing the behavior as well as the species of an animal with the help of residual traces left in the surroundings. Also, it has its importance in medicine. The trace reasoning is essentially different in its methodology from that of the contemporary natural sciences within the Galilean paradigm. The difference consists in the radical importance of an individual as an individual as opposed to common regularities in nature studied by the natural sciences. Thus the circumstantial reasoning bears distinctively anthropocentric character. The theoretical analysis of this kind of reasoning may be helpful to overcome the tension between rationalism and irrationalism.